Integration of Digital Payment Literacy and Accounting in Promoting the Growth of MSMEs - Hernianti Harun; Nurain, Nurain; Nurwani, Nurwani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The advancement of Micro, Small, and Medium Enterprises (MSMEs) is increasingly shaped by digital transformation and financial literacy, particularly through the integration of e-commerce payment systems and accounting practices. Specific Background: MSMEs assisted by the Parepare City Labour Office encounter notable challenges in adopting digital transactions and managing financial records, limiting their growth potential. Knowledge Gap: Prior research has insufficiently explored the combined effect of e-commerce payment methods and accounting literacy on MSME growth, especially in government-supported local business settings. Objective: This study investigates how e-commerce payment adoption and accounting literacy influence the growth of MSMEs guided by the Parepare City Manpower Office. Methods: Employing a quantitative approach, 60 MSMEs were sampled from a population of 150 using the Slovin formula (10% margin of error). Data were collected via questionnaires and analysed using SPSS v30 through validity, reliability, multiple linear regression, t-tests, F-tests, and determination coefficient analysis. Results: Both e-commerce payment methods (p = 0.000) and accounting literacy (p = 0.019) significantly affect MSME growth, with joint influence confirmed by the F-test (p = 0.000). Novelty: The study offers a nuanced understanding of how digital and financial competencies synergistically promote MSME growth. Implications: Strengthening MSME capacity in digital payments and accounting literacy is vital for fostering resilience and competitiveness in the digital economy.